Ocular Pharmacological Profile of Hydrocortisone in Dry Eye Disease - Bucolo, Claudio; Fidilio, Annamaria; Fresta, Claudia Giuseppina; Lazzara, Francesca; Platania, Chiara Bianca Maria; Cantarella, Giuseppina; Di Benedetto, Giulia; Burgaletto, Chiara; Bernardini, Renato; Piazza, Cateno; Barabino, Stefano; Drago, Filippo (Frontiers in Pharmacology, 2019)
To investigate the ocular pharmacological profile of hydrocortisone (HC) using in vitro and in vivo models of dry eye disease, rabbit corneal epithelial cells (SIRCs) were used to assess the effect of HC in two paradigms of corneal damage: hyperosmotic stress and scratch-wound assay. Dry eye was induced in albino rabbits by topical administration of atropine sulfate or by injection of concanavalin A (ConA) into the lacrimal gland. TNFα, TNF-related apoptosis-inducing ligand (TRAIL), IL-1β, and IL-8 were determined by ELISA or Western blot in a corneal damage hyperosmotic in vitro model, with or without HC treatment. Inflammatory biomarkers, such as TNFα, IL-8 and MMP-9, were evaluated in tears of rabbit eye injected with ConA and treated with HC. Tear volume and tear-film integrity, in both in vivo models, were evaluated by the Schirmer test and tear break-up time (TBUT). Ocular distribution of four formulations containing HC (0.001%; 0.003%; 0.005% and 0.33%) was performed in the rabbit eye. Aqueous humor samples were collected after 15, 30, 60 and 90 min from instillation and then detected by LC-MS/MS. Hyperosmotic insult significantly stimulated protein expression of inflammatory biomarkers, which were significantly modulated by HC treatment. HC significantly enhanced the re-epithelialization of scratched SIRCs. Topical treatment with HC significantly reduced the tear levels of TNF-α, IL-8 and MMP-9 vs. vehicle in the ConA dry-eye model. Moreover, HC significantly restored the tear volume and tear-film integrity to levels of the control eyes, both in ConA- and atropine-induced dry eye paradigms. Finally, we demonstrated that HC crossed, in a dose-dependent manner, the corneal barrier when the eyes were topically treated with HC formulations (dose range 0.005-0.33%). No levels of HC were detected in the aqueous humor after topical administration of the formulation containing the lowest dose of the drug (0.001%), suggesting that, at this very low concentration, the drug did not cross the corneal barrier avoiding potential side effects such as intraocular pressure rise. Altogether, these data suggest that HC, at very low concentrations, has a relevant anti-inflammatory effect both in vitro and in vivo dry eye models and a good safety profile.